2010
DOI: 10.1103/physrevb.81.212301
|View full text |Cite
|
Sign up to set email alerts
|

Exciton-seeded multiphoton ionization in bulkSiO2

Abstract: In a femtosecond pump-probe experiment the pump pulse injects a modest density of free carriers by multiphoton absorption. Measuring the nonlinear absorption of the probe pulse we observe exciton-seeded multiphoton ionization. The excitons self-trap in SiO 2 in Ͻ300 fs following free-carrier injection and decay biexponentially with lifetimes of 34Ϯ 8 and 338Ϯ 67 ps at room temperature. The extent of the probe-pulse absorption provides a model-independent demonstration that avalanche ionization plays a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 18 publications
(22 reference statements)
7
73
0
Order By: Relevance
“…A higher IR fluence provides more avalanche ionization and can re-excite more free electrons from STEs, and therefore, a lower UV threshold is observed. It is found that with a high IR fluence (2.1 J/cm 2 ), the UV damage threshold returns to its normal value at a delay of ~27.3 ps, which is similar to the lifetime of STEs in accordance with previous results [15]. Since damage forms as a combined effect of UV and IR pulses, the damage size is determined by the size of the area where the two beam overlap.…”
Section: Reduction Of Uv Damage Thresholdsupporting
confidence: 71%
“…A higher IR fluence provides more avalanche ionization and can re-excite more free electrons from STEs, and therefore, a lower UV threshold is observed. It is found that with a high IR fluence (2.1 J/cm 2 ), the UV damage threshold returns to its normal value at a delay of ~27.3 ps, which is similar to the lifetime of STEs in accordance with previous results [15]. Since damage forms as a combined effect of UV and IR pulses, the damage size is determined by the size of the area where the two beam overlap.…”
Section: Reduction Of Uv Damage Thresholdsupporting
confidence: 71%
“…We propose that in our experiment a breaking of excitons occurred due to collisions with high energetic electrons within the conduction band. The interpretation is supported by other studies, where it has been shown that excitons, which were formed by low-fluence XUV radiation, can be destroyed by multiphoton absorption of a near-infrared pulse 46 .…”
Section: Resultssupporting
confidence: 76%
“…However, the lifetime of exciton-polaritons is limited to a fraction of a picosecond by their phonon assisted relaxation to indirect exciton states decoupled from light. 25 These indirect excitons are essentially immobile. They are easily self-trapped and live for several microseconds or even longer.…”
mentioning
confidence: 99%